Pyridinic Nitrogen‐Enriched Carbon Nanogears with Thin Teeth for Superior Lithium Storage. Issue 18 (30th June 2016) - Gu, Jianan; Du, Zhiguo; Zhang, Chao; Yang, Shubin
Abstract : Pyridinic nitrogen‐enriched carbon nanogears (PNCG) are achieved via controllable synthesis of a well‐defined polyimide and subsequent pyrolysis at tunable temperatures. The resultant PNCG possesses unique structural and compositional characteristics, which significantly promote the fast transports of both lithium and electron. Consequently, the optimal pyridinic nitrogen‐enriched carbon nanogears exhibit a very high reversible capacity and long cycle life for lithium storage.